Personal Hygiene and its Effect on the Treatment of After Cesarean Section Debridement in NTB General Hospital (Indian Journal of Forensic Medicine & Toxicology, 2020)
Personal hygiene is important for after cesarean patients because personal hygiene will affect one’s healthand psychological well-being. Patients with after cesarean wounds should be given immediate wound care bycleaning to prevent infection during the wound care. This will affect the wound healing process in cesareansurgery patients. This study aims to determine the relationship between personal hygiene and healing ofafter cesarean wounds in the NTB General Hospital. An accidental sampling technique of 52 patients withafter cesarean section who experienced personal hygiene during wound care in the NTB General Hospitalwas used in this study using a prospective cohort study design. By using data analysis based on the chisquare test, the results showed that personal hygiene in after cesarean patients was mostly good category of40 respondents (76.9%), cesarean section wound healing in after cesarean patients most of the categorieswere cured as much as 46 respondents (88.5%) and obtained a p-value of 0.002 <0.05. The results of thestudy confirmed the relationship between personal hygiene and healing of after cesarean wounds in theNTB General Hospital. This study recommends that nurses and other health teams develop theories andguidelines for the implementation of personal hygiene that are more effective and efficient in order to reduceinfection after cesarean section.